The Differences Effect Of Corn Hair Tea And Rajuke Tea On The Production Of Breast Milk In The Working Area Of Puskesmas Kota Selatan , Puskesma Kota Utara And Puskesmas Sipatana In Gorontalo City - Nurnaningsih Ali Abdul; Nancy Olii (Science Midwifery, 2021)
In 2018 in Gorontalo Province there were three health centers with the lowest breastfeeding coverage, Sipatana Public Health Center (33.9%), Kota Utara (23.8%), and Kota Selatan (16.6%). The results showed that the antioxidant content in the form of alkaloids and sterols can increase the production of breastmilk. This substance is contained in the combination tea of ​​Corn Hair and Moringa leaves (Rajuke). This study aimed to analyze the different effect of corn hair tea and Rajuke tea on breastmilk production in postpartum mothers.This research was pre-experimental with a control group pretest-posttest design which was carried out from August to November 2020 with number of sample were 60 postpartum motehrs. Respondents were divided into 2 groups, each group was given tea for 7 consecutive days and a breast pump. Data analysis used univariate and bivariate analysis using paired t-test. The results showed that Rajuke tea was more able to increase breastmilk production comparing to Corn Hair tea (0.86). The midwives are expected to provide promotion and education about foodstuffs that can increase breastmilk production by utilizing local ingredients.